Dislocation driven spiral and non-spiral growth in layered chalcogenides. Issue 31 (27th July 2018) - Nie, Yifan; Barton, Adam T.; Addou, Rafik; Zheng, Yongping; Walsh, Lee A.; Eichfeld, Sarah M.; Yue, Ruoyu; Cormier, Christopher R.; Zhang, Chenxi; Wang, Qingxiao; Liang, Chaoping; Robinson, Joshua A.; et al.
Abstract : Evidence from simulations and experiments reveals the mechanistic similarities between concentric growth and spiral growth. Abstract : Two-dimensional materials have shown great promise for implementation in next-generation devices. However, controlling the film thickness during epitaxial growth remains elusive and must be fully understood before wide scale industrial application. Currently, uncontrolled multilayer growth is frequently observed, and not only does this growth mode contradict theoretical expectations, but it also breaks the inversion symmetry of the bulk crystal. In this work, a multiscale theoretical investigation aided by experimental evidence is carried out to identify the mechanism of such an unconventional, yet widely observed multilayer growth in the epitaxy of layered materials. This work reveals the subtle mechanistic similarities between multilayer concentric growth and spiral growth. Using the combination of experimental demonstration and simulations, this work presents an extended analysis of the driving forces behind this non-ideal growth mode, and the conditions that promote the formation of these defects. Our study shows that multilayer growth can be a result of both chalcogen deficiency and chalcogen excess: the former causes metal clustering as nucleation defects, and the latter generates in-domain step edges facilitating multilayer growth. Based on this fundamental understanding, our findings provide guidelines for the narrow window of growth conditions which enables large-area, layer-by-layer growth.